2000
DOI: 10.1128/jvi.74.22.10699-10706.2000
|View full text |Cite
|
Sign up to set email alerts
|

Viral Vascular Endothelial Growth Factor Plays a Critical Role in Orf Virus Infection

Abstract: Infection by the parapoxvirus orf virus causes proliferative skin lesions in which extensive capillary proliferation and dilation are prominent histological features. This infective phenotype may be linked to a unique virus-encoded factor, a distinctive new member of the vascular endothelial growth factor (VEGF) family of molecules. We constructed a recombinant orf virus in which the VEGF-like gene was disrupted and show that inactivation of this gene resulted in the loss of three VEGF activities expressed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
117
1
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(126 citation statements)
references
References 44 publications
5
117
1
3
Order By: Relevance
“…The vVEGF genes of PPVs are orthologues of mammalian VEGF gene family members, which stimulate proliferation and permeability of vascular endothelial cells and induce angiogenesis by binding to a set of mammalian tyrosine kinase receptors (Ferrara, 2004). It was demonstrated that all VEGFs of established PPV species (including PCPV VR634; Ueda et al, 2003) also possess the ability to induce endothelial proliferation and angiogenesis and are likely to be responsible for the highly vascularized and proliferative nature of PPV lesions (Savory et al, 2000;Wise et al, 2003;Inder et al, 2007;Ueda et al, 2003Ueda et al, , 2007. This is in spite of the fact that sequence variation of vVEGF proteins is remarkably high, varying from 35 to 63 % aa identity between species, whilst isolates of the same species show as little as 38 % aa sequence identity (Lyttle et al, 1994;Mercer et al, 2002Mercer et al, , 2006Wise et al, 2003Delhon Fig.…”
Section: Hautaniemi and Othersmentioning
confidence: 99%
“…The vVEGF genes of PPVs are orthologues of mammalian VEGF gene family members, which stimulate proliferation and permeability of vascular endothelial cells and induce angiogenesis by binding to a set of mammalian tyrosine kinase receptors (Ferrara, 2004). It was demonstrated that all VEGFs of established PPV species (including PCPV VR634; Ueda et al, 2003) also possess the ability to induce endothelial proliferation and angiogenesis and are likely to be responsible for the highly vascularized and proliferative nature of PPV lesions (Savory et al, 2000;Wise et al, 2003;Inder et al, 2007;Ueda et al, 2003Ueda et al, , 2007. This is in spite of the fact that sequence variation of vVEGF proteins is remarkably high, varying from 35 to 63 % aa identity between species, whilst isolates of the same species show as little as 38 % aa sequence identity (Lyttle et al, 1994;Mercer et al, 2002Mercer et al, , 2006Wise et al, 2003Delhon Fig.…”
Section: Hautaniemi and Othersmentioning
confidence: 99%
“…Recently, it was suggested that BPSV, PCPV and PVNZ do not harbour an ORFV-like IL-10 gene (Fleming et al, 2000). Data on the presence of the VEGF-E gene in PPV other than ORFV do not exist.…”
mentioning
confidence: 99%
“…Potential ORFV virulence genes include an interferon-resistance gene, which is a homologue of the vaccinia virus (VACV) E3L gene (Haig et al, 1998;McInnes et al, 1998), and a functional dUTPase (Cottone et al, 2002). The right end of the ORFV genome shows greater variability than the left end and is composed of genes that are not found in other poxviruses including a viral interleukin (IL)-10 (Fleming et al, 1997(Fleming et al, , 2000Imlach et al, 2002), a factor (GIF) inhibiting granulocyte macrophage colony stimulating factor and interleukin-2 activity (Deane et al, 2000;Haig et al, 1996), and a new member of the vascular endothelial growth factor (VEGF) family (Haig & Mercer, 1998;Lyttle et al, 1994), designated VEGF-E . The latter mediates angiogenesis in vitro and in vivo and is therefore thought to be responsible for the induction of proliferative bloody lesions Ogawa et al, 1998;Savory et al, 2000;Wise et al, 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1A), seven have been described previously in ORFV (Fraser et al, 1990;Lyttle et al, 1994;Sullivan et al, 1995a;Fleming et al, 1997;McInnes et al, 2001;Rziha et al, 2003), two are orthologues of VACV genes and the remaining five appear unrelated to anything in the nucleotide or protein databases. Only two of the ORFV genes have had a function ascribed to them: those encoding the viral vascular-endothelial growth factor (VEGF) and viral IL-10 (Meyer et al, 1999;Wise et al, 1999;Fleming et al, 2000;Savory et al, 2000;Imlach et al, 2002). The remaining five, together with the five unknown genes reported here, have not been functionally characterized.…”
mentioning
confidence: 99%